2015
DOI: 10.1109/tnsre.2014.2360533
|View full text |Cite
|
Sign up to set email alerts
|

Illusory Sense of Human Touch From a Warm and Soft Artificial Hand

Abstract: To touch and be touched are vital to human development, well-being, and relationships. However, to those who have lost their arms and hands due to accident or war, touching becomes a serious concern that often leads to psychosocial issues and social stigma. In this paper, we demonstrate that the touch from a warm and soft rubber hand can be perceived by another person as if the touch were coming from a human hand. We describe a three-step process toward this goal. First, we made participants select artificial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Prosthesis consumers value skin-like coverings for their prosthetic devices that have a similar look and feel as real skin as well as good durability 8 . It has been shown that, by tuning the modulus, viscoelasticity and temperature of a skin-like coating, the touch from a prosthetic hand can be indistinguishable from a real hand 26 . Restoring both sensory feedback and the mechanical properties of natural skin may allow patients to comfortably use their devices during intimate interactions (for example, when interacting with children) 7 .…”
Section: Mimicking Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Prosthesis consumers value skin-like coverings for their prosthetic devices that have a similar look and feel as real skin as well as good durability 8 . It has been shown that, by tuning the modulus, viscoelasticity and temperature of a skin-like coating, the touch from a prosthetic hand can be indistinguishable from a real hand 26 . Restoring both sensory feedback and the mechanical properties of natural skin may allow patients to comfortably use their devices during intimate interactions (for example, when interacting with children) 7 .…”
Section: Mimicking Mechanical Propertiesmentioning
confidence: 99%
“…However, to fully mimic the feel and sensory properties of skin, it is important to implement materials with low elastic moduli and good stretchability 26 . On average, biological skin is stretchable to 75% strain 34 , and this allows free movement of the joints, which experience surface strains up to 55% for the knees 35 .…”
Section: Mimicking Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We use an anthropomorphic android robot designed after a human both in terms of appearance and functionality, to such an extent that the hands have heating pads inside the palms so as to give a feeling of human touch [2]. For this experiment, both the robot hand and a human test subject's hand were covered with a white butler glove as shown in Fig.…”
Section: Experiments Setupmentioning
confidence: 99%
“…Based on our everyday tactile observations described above, we can expect that R c depends on surface roughness, applied force, as well as mechanical and thermal properties of the skin and the contacting material. Since quantifying the contact resistance is important for design of electronics [2][3][4][5][6], thermal displays [7], artificial hands [8], haptic devices [9], and wearable thermoelectric devices [10,11], it is important to know how to combine these physical parameters to model the value of R c .…”
mentioning
confidence: 99%